Análisis jurídico de las marcas blancas en los productos del Supermercado AKI de la ciudad de Guaranda, provincia Bolívar, periodo 2021. - Naranjo Carrasco, Anthony Rolando (2023)
In the present investigation, a legal analysis of the term "white label" is carried out, which in the commercial world, refers to products, sold by "retail distributors" in supermarkets under the same distributor brand or another brand. In other words, it is created by the distributor, usually through an exclusive product sales agreement between the manufacturer and the retailer. This is the case of the Aki supermarket, in the city of Guaranda, where various products with the "Aki brand" are displayed. The problem arises around the protection of the brand, due to the fact that the Ecuadorian legislation does not correctly regulate the problems that may arise around the use of a white brand. Because there may be violations of the intellectual property of the other brands that are spent in the supermarket, they manifest civil, criminal or administrative actions. Therefore, the main objective of this research is to legally analyze the white brands in products from the Aki supermarket in the city of Guaranda, Bolívar Province. The selected study has a qualitative methodology, because it originates from an interpretive approach. It was selected for allowing an efficient and creative process, which allows the extraction of knowledge from a heterogeneous data set in narrative or textual form. The inductive method was used with descriptive and qualitative research, the data collection instruments were based on a survey and an interview. The same that allowed the collection, selection and analysis of the data found. After reviewing the different national regulations, it was concluded that the definition of white marks is not found in the regulations. But rather on the doctrine that white brands are little- 19 known products with simple packaging and designs. One of the main characteristics of this type of product is that the price and quality of the product are much lower than the rest of the products on the market. They will also adopt the name and popularity of the distributor. Keywords: Legal Analysis, White Labels, Products, Aki Supermarket, Violation.